2018
DOI: 10.21149/10182
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccine acceptance is high among adults in Mexico, particularly in people living with HIV

Abstract: Objective. To measure HPV vaccine acceptance in diverse Mexican adult populations, taking into account HIV status. Materials and methods. A total of 1 329 men and women, with and without HIV, participated in one of three intervention studies, offering HPV vaccination, carried out in the states of Morelos, Tlaxcala and Mexico City; either the bivalent (Morelos n=103, Tlaxcala n=127) or quadrivalent HPV-vaccine (Mexico City n=1 099) was offered. Results. HPV vaccine was accepted by 80.3% of participants; accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Human papilloma virus (HPV) infection, which is sexually transmitted to both males and females, is a global epidemic (1)(2)(3). Approximately 75% of sexually active individuals encounter HPV at some time in their lives (4).…”
Section: Introductionmentioning
confidence: 99%
“…Human papilloma virus (HPV) infection, which is sexually transmitted to both males and females, is a global epidemic (1)(2)(3). Approximately 75% of sexually active individuals encounter HPV at some time in their lives (4).…”
Section: Introductionmentioning
confidence: 99%
“…This finding echoes what other studies have observed regarding high levels of HPV vaccine acceptance even in instances of low-level awareness and knowledge about HPV, cervical cancer or vaccination. [11][12][13] In Mexico, the high acceptability of the vaccine among women has also been documented, 14 however, the need to promote knowledge about the benefits of the vaccine is also recognized. 15 An additional recommendation that could be offered to women to increase acceptability is to spread the message that the vaccine not only helps them but also their partners in the future cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 24 articles included in this study, 23 were cross-sectional studies [18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], and 1 was a cohort study [23]. A total of 14,466 participants were included.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the questionnaires were administered face-to-face (21 out of 24), one was administered through an online survey, one was administered through phone call and finally one was administered through a combination of telephone/face-to-face questionnaire. Geographically, the studies were distributed as follows: 7 from Mexico [20,30,32,38,39,41], 5 from Puerto Rico [23-25, 35, 40], 5 from Argentina [18,19,21,22,29] [36,37], 1 from Peru [33], and 1 from Haiti [31]. The different studies evaluated the acceptance rate of HPV vaccine in multiple populations.…”
Section: Study Characteristicsmentioning
confidence: 99%